(3GdGJHGY hGdJhcjOs - (3YHO GdhGMO Hf Ydj GdMdHj, CHh GdWjH GddZhj, J (B351 (3g` s
(3ChdgG (B:s
(3bGd YHO GdhGMO Hf Ydi (B: (3gPG cJGH GdGJHGY hGdJhcjO , OYGfG Edi JCdjaI EZaGd SdafG EaQGO cJGH ajgeG TGa ai GSJjYGHgeG bGd HYVge hbO SFd Yf cdeI ef GdGJHGY eG eYfGgG abGd (B: (3TF fHJOF Hg cdGefG s
(3BNQgG (B:s
(3ef HGH GdJhcjO bhdg(B: (3jbGd CQV NQGH jHGH , hHdO NQGH jHGH hGdNQGH hGdjHGH hGMO , bGd GdTGYQ (B: (3aQeGg GdReGf efg HUQa ZGOQ GdeQJY GdNUjH HGHG BNQg HMeO Gddg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYeI (B_ (3GdQHGW (B(505(3O(B) s
Keywords: (3GddZIs